KAJIAN KESEHATAN IKAN KURISI (Nemipterus sp.) Di TPI KABUPATEN TUBAN BERDASARKAN HISTOLOGI HATI DAN INSANG - Dwi Oktafitria (Universitas PGRI Semarang, 2018)
The purpose of this research is to know the condition of fish health of kurisi (Nemipterus sp.) As fish of public consumption which sold in TPI of Tuban Regency seen from the histology of liver and gill damage in order to maintain the survival and existence of the fish in the sea as one source of animal protein in the fulfillment of community nutrition. This research used descriptive method to histology of liver and gill fish Nemipterus sp. taken from the 2 largest TPI in Tuban Regency located near the sea port (Jetty) namely TPI Bancar and TPI Glondong Gede. Fish sampling (Nemipterus sp.) Was done randomly and then made histology preparation using paraffin method. Based on the research results obtained from liver samples is known that Kurisi fish is at the level of 0-IV damage whereas in gill samples are known all of them damaged up to necrosis. So it can be concluded that the health condition of fish kurisi (Nemipterus sp.) In TPI Bancar and TPI Glondonggede can still be said to be healthy although in histology observation result of liver and gill there are many damage not yet heavy.